An Exploratory Study Examining the Inclusion of Children with Autism in Primary Schools in Ireland - Garcia Albarran, Eva Maria (Trinity College Dublin. School of Social Work & Social Policy. Discipline of Social Studies, 2023)
Children with Autism are frequently the recipients of separating practices and exclusion from regular schools. Despite the international and national agreements supported by research evidence concerning inclusive education, the gap between policy and practice is still a work in progress. Different aspects influence the inclusion of children with Autism at a macro, meso and micro level. Ultimately, the day to day at the school micro level (i.e., classroom, playground and support classroom) is what sharpens their journey. In addition, previous studies have pointed to the relevance of interactions to explore inclusion in the primary school years. Moreover, interactions are the basic blocks of relationships, relevant for students' academic, social and emotional development in school. Therefore understanding what happens in the daily interactions between children with Autism and the other education actors could shed light on how to implement inclusive education, helping to reduce the gap between policy and practice. This small-scale, qualitative, multiple-embedded case study research explores the interactions between eight children with Autism and the relevant actors in three in-school settings through observations. The triangulation of participants and settings illuminates the similarities and differences in the interactions, adding knowledge on what enabled and inhibited the inclusion of children with Autism in schools. The key message from the research findings is that the interconnection between interactions involving support towards participation appears as a strong facilitator for the inclusion of children with Autism in all in-school settings. The research reveals the essential role of interactions among all participants in facilitating or inhibiting the inclusion of the eight children with Autism in their schools. In particular, it emphasises the interactions between teachers and children with Autism as the bridge for further interactions. It highlights that for participation to be successful, it must be underpinned by appropriate support and embedded within the teaching plan and practice of the classroom. It demonstrates that the participation of children with Autism with their classmates is key for further interactions and, thus, a successful inclusive education. It also reveals the essential role of the context bounding each in-school setting as a bridge to facilitate interactions and participation (e.g., children's position in the classroom and rest areas). This study goes deeper in providing a novel approach to the study of inclusion in practice using a close perspective of the interactions among the education actors while applying a systemic frame to the study by including three different school settings. With this novel approach, the thesis contribution to knowledge reveals first the implementation of a systemic approach to research at the school micro level, which facilitated an understanding of school dynamics and the nuances and complexities emerging in practice. Secondly, the focus content acknowledges interactions, support and participation as three intertwined dimensions, showing how the interactions in the settings reveal different paths that appear to be associated with the level of support and participation, which at the same time shed light on paths that enable and inhibit inclusion. The findings have implications for research, policy and practice. It appeared that, for inclusive education to materialise in practice (i.e., to provide children with Autism with access, presence, participation, achievement and belonging to the school communities), they must be placed in the classroom with the right support approach to enable their participation alongside their peers. This approach requires teachers to interact with children directly, embedding their teaching and learning within the classroom plan. In addition, it requires SNAs to be deployed to facilitate the participation and learning of children with Autism in all activities alongside their peers. Furthermore, it requires understanding the important role of peers' interactions in the inclusion of children with Autism in regular schools and their communities.
APPROVED
Keywords: Ireland; Children with Autism; Inclusive Education; Primary Schools